2021
DOI: 10.3389/frobt.2021.744526
|View full text |Cite
|
Sign up to set email alerts
|

10 Years of Human-NAO Interaction Research: A Scoping Review

Abstract: The evolving field of human-robot interaction (HRI) necessitates that we better understand how social robots operate and interact with humans. This scoping review provides an overview of about 300 research works focusing on the use of the NAO robot from 2010 to 2020. This study presents one of the most extensive and inclusive pieces of evidence on the deployment of the humanoid NAO robot and its global reach. Unlike most reviews, we provide both qualitative and quantitative results regarding how NAO is being u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 160 publications
(220 reference statements)
0
19
0
Order By: Relevance
“…The selection of the child-sized humanoid robot NAO was based on the fact that is one of the most popular and researched humanoid robots worldwide and it is predominantly used in child robot-assisted interventions (Amirova et al, 2021 ; Papakostas et al, 2021 ). NAO is able to apply verbal and nonverbal communication using polytropic sensors, such as cameras and microphones, and is widely preferred due to its flexible movement and its multi-coloured eyes (Kumazaki et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The selection of the child-sized humanoid robot NAO was based on the fact that is one of the most popular and researched humanoid robots worldwide and it is predominantly used in child robot-assisted interventions (Amirova et al, 2021 ; Papakostas et al, 2021 ). NAO is able to apply verbal and nonverbal communication using polytropic sensors, such as cameras and microphones, and is widely preferred due to its flexible movement and its multi-coloured eyes (Kumazaki et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…This could occasionally cause disturbance and disappointment to the child, but the special educator would still not take NAO’s place in tutoring so as to minimize the effect of the educator during the SR-tutored intervention. Speech recognition, especially in the setting of interaction with children, has already been identified as one of NAO’s weaknesses [ 24 ]. Integration of more advanced speech recognition softwares to complete/ameliorate NAO’s speech recognition could be considered for future works, especially for children and for populations without normal social and communication abilities.…”
Section: Discussionmentioning
confidence: 99%
“…The social robot NAO was selected for the robot-tutored sessions ( Figure 1 ). The applicability and effectiveness of this robot have been well-established after more than ten years of human–NAO interaction and around 300 research works reporting its usage in several different daily life settings [ 24 ]. NAO is also frequently used in educational robotics research settings [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, we found that abilities to sense the whole classroom were proposed for social drones by participants which is quite specific to the drone’s ability to adopt a bird’s-eye position and see the entire class (see Section 6.1.4 ). Having said that, improving social expressivity of social drone is needed as they lack anthropomorphic features used by other social robots in education [e.g., NAO Amirova et al (2021) ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of social robots in education, many researchers have worked on investigating interactions using different robotic platforms that are already available in the market, such as the popular NAO robot [ Johal (2020) ; Amirova et al (2021) ]. For example, Serholt et al (2014) deployed a NAO robot to investigate the school children’s response to a robotic tutor compared with a human tutor while giving instructions to accomplish a task.…”
Section: Related Workmentioning
confidence: 99%